Knights - Corbin, Carole Lynn. (New York : F. Watts, 1989)
Describes the training, behavior, equipment, and typical daily life of a knight in medieval times.
The training of knights -- What a knight needed -- Castles -- Life in the castle -- A day in the castle -- War games -- Chivalry.
Includes bibliographical references (p. 60) and index.
Elem. School Library Collection.
Wilson's Junior High School.
5.8
5-8
Keywords: Civilization, Medieval -- Juvenile literature; Knights and knighthood -- Juvenile literature; Civilization, Medieval; Knights and knighthood; Knights and knighthood; Medieval civilization